THE EFFECT OF OIL CONTENT IN SEDIMENTS ON THE MIXTURE OF MACROZOOBENTHOS IN INTERTIDAL ZONE OF SEA WATER OF DUMAI RIAU PROVINCE - Ahmad Faisal Daulay; Yusni Ikhwan Siregar; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in January 2018 in the Dumai sea waters of Riau Province with the aim to determine the oil content in sediments, the abundance of macrozoobenthos, and the effect of oil content on sediments on the abundance of macrozoobenthos. The research location is divided into 5 stations, from each station consisting of one transect line and each transect line consists of 3 plots (1m x 1m). Taking sediment samples using a pipe (pvc) while taking macrozoobenthos samples with the help of a small shovel. The results of the study obtained an average oil content in the sediment of 73.86 ppm. The abundance of macrozoobenthos varies per station with a range of 35,00 ind/m2– 69,33 ind/m2. The macrozoobenthos species found consisted of 15 species with phyla, and 5 classes. The relative abundance value of macrozoobenhtos varies from 2,88% to 24,79%. Based on simple linear regression, the effect of oil content on sediments on the abundance of macrozoobenthos is very strong (R2= 0,761); (r) = 0,87. The abundance of macrozoobenthos is influenced by the oil content in the sediment of 76,1% and the rest is influenced by other factors such as predators, competition, and food reserves. Keywords: Pollution, Macrozoobenthos, Sediment oil content